2021
DOI: 10.4049/jimmunol.2100125
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Uba1 Degrades IRF3 through K48-Linked Ubiquitination to Inhibit IFN Production

Abstract: Fish IFN regulatory factor 3 (IRF3) is a crucial transcription factor in the IFN activation signaling pathway, which leads to IFN production and a positive cycle. Unrestricted IFN expression results in hyperimmune responses and therefore, IFN must be tightly regulated. In the current study, we found that zebrafish Ub-activating enzyme (Uba1) negatively regulated IRF3 via the K-48 ubiquitin proteasome degradation of IRF3. First, ifn expression stimulated by spring viraemia of carp virus infection was blunted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Some of the identified somatic variants were also on functional residues (S478, R551, N606, S621, R747), one of which is a partial loss of function site (R747). The literature and prevalence in public databases on the identified putative somatic variants are summarized in Table 2 [7,20,33,[35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the identified somatic variants were also on functional residues (S478, R551, N606, S621, R747), one of which is a partial loss of function site (R747). The literature and prevalence in public databases on the identified putative somatic variants are summarized in Table 2 [7,20,33,[35][36][37][38][39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…We found that HDAC5 promoted the transcriptional activity of IFN-β stimulated by these plasmids, respectively ( Figure 4 A–F). IRF3 is essential for IFN-β expression and the antiviral response [ 29 , 30 , 31 ]. Compared with the control groups, the overexpression of HDAC5 remarkably promoted the phosphorylation of IRF3 upon FMDV infection ( Figure 4 G).…”
Section: Resultsmentioning
confidence: 99%
“…A similar phenomenon has been shown to regulate activation of NF-κB in Drosophila , where IMD is proteasomally degraded owing to permanent presence of Ub K48 linkages, which are lost upon bacterial infection thereby stabilizing the protein and activating the pathway [ 26 , 27 ]. Likewise, Uba1-mediated proteasomal degradation of IRF3 in Zebrafish keeps activation of IFN signaling and activation of anti-viral immune response in check [ 44 ]. While our findings are consistent with a potential direct role for the proteasome in stabilizing factors that may be necessary for ORR/IPR induction, we cannot rule out that the bounce-back response pathway may also act in parallel.…”
Section: Discussionmentioning
confidence: 99%